(untitled) (Swiss Medical Weekly, 2015)
OBJECTIVE: The prevalence of ragweed allergy is increasing worldwide. Ragweed distribution and abundance is spreading in Europe in a wide area ranging from the Rhone valley in France to Hungary and Ukraine, where the rate of the prevalence can peak at as high as 12%. Low-grade ragweed colonisation was seen in Geneva and Ticino, less than two decades ago. There were fears that allergies to ragweed would increase Switzerland. The intent of this study was to assess the rate of prevalence of sensitisation and allergy to ragweed in the population living in the first rural Swiss setting where ragweed had been identified in 1996, and to evaluate indirectly the efficacy of elimination and containment strategies. MATERIAL AND METHODS: In 2009, 35 adults in a rural village in the Canton of Geneva were recruited. Data were collected by means of questionnaires and skin-prick tests were done on each participant. The study was approved by the local Ethics Committee. RESULTS: Based on questionnaires, 48.6% had rhinitis (95% confidence interval [CI] 32.9–64.4; n = 17/35) and 17.1% asthma (95% CI 8.1–32.6; n = 6/35). Atopy was diagnosed in 26.4% (95% CI 12.9–44.4) of the sample (n = 9/34). Ragweed sensitisation was found in 2.9% (95% CI 0.7–19.7; n = 1/34), mugwort sensitisation in 2.9% (95% CI 0.1–14.9; n = 1/35), alder sensitisation in 17.1% (95% CI 6.6–33.6; n = 6/35), ash sensitisation in 12.5% (95% CI 3.5–29.0; n = 4/32) and grass sensitisation in 22.9% (95% CI 10.4–40.1; n = 8/35). Ragweed (95% CI 0.1–14.9; n = 1/34) and mugwort allergies (95% CI 0.1–14.9; n = 1/35) were both found in 2.9% of the population. CONCLUSION: This study showed a surprisingly low incidence of ragweed sensitisation and allergy, of 2.9% and 2.9%, respectively, 20 years after the first ragweed detection in Geneva. The feared rise in ragweed allergy seems not to have happened in Switzerland, compared with other ragweed colonised countries. These results strongly support early field strategies against ragweed.